Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm given $x^2+2x-4$ at $x=2$ and I have to find the tangent line to this curve at that point...

share|improve this question
1  
You should essentially differentiate the quadratic $x^2 + 2x -4$ w.r.t. $x$ and plug in $x=2$. But since you have tagged this "precalculus", do you know how to differentiate a (polynomial) function? –  Srivatsan Dec 17 '11 at 3:44

2 Answers 2

Here's an algebraic approach that avoids the explicit use of derivatives.

We are given a quadratic function $f(x) = x^2 + 2x -4$, and we want to find the equation of the tangent to the parabola $y = f(x)$ at the point $(2, 4)$. (Note that $f(2) = 2^2 + 2 \cdot 2 - 4 = 4$.) Assume that it is given by the equation $$ y = m(x-2) + 4, \tag{$\ast$} $$ where $m$ is its slope.

Let's consider the intersection of the parabola with the tangent; this is given by the system of equations $$ \begin{cases} y &=& x^2 + 2x - 4, \\ y &=& m(x-2)+4. \end{cases} $$ In other words, to find the intersection, we should solve the quadratic equation $ x^2 + 2x - 4 = m(x-2)+4$, or $$ x^2 + (2-m)x+(2m-8) = 0. \tag{$\ast\ast$} $$ using the quadratic formula like so $$ \frac{-(2-m)\pm\sqrt{(2-m)^2-4.1.(2m-8)}}{2.1} $$ Pictorially it is clear that the tangent meets the parabola meets in exactly one point, so we want $(\ast \ast)$ to have a unique solution. This implies that the discriminant of $(\ast \ast)$ vanishes: $$ \begin{array}{crcl} &(2-m)^2 - 4 \cdot (2m-8) &=& 0 \\ \implies \qquad & m^2 - 12m + 36 &=& 0. \end{array} $$ Conveniently (although this is not a numerical coincidence), this equation has a unique solution $m=6$: this is the solution we are after. Plugging $m=6$ in $(\ast)$, we get the equation of the tangent at $(2, 4)$ to be $y = 6x-8$.

share|improve this answer
    
Thanks this was very helpful –  Max Dec 17 '11 at 4:13

Another method that can be used which is traditionally taught before derivatives is the limit (they're very similar but this is more intuitive):

Let $f(x) = x^2 + 2x - 4$ and $f'(x)$ be the tangent line at any point $a$ on the curve $f(x)$

Difference quotient:

$$f'(x) =\lim_{h \rightarrow 0}\frac{f(a + h) - f(a)}{h}$$

What this essentially means is that we we take the slope between two points $a$ and $a+h$ as $h$ gets very small or as $h\rightarrow0$ the point $a+h$ gets closer to $a$ until there mathematically the slope is tangent to the point $a$.

$$f'(x) =\lim_{h \rightarrow 0} \frac{[(a+h)^2+ 2(a+h) - 4] - [(a)^2 - 2(a) - 4]}{h} $$ $$=\lim_{h \rightarrow 0} \frac{[(h^2 + 2ah + a^2) + (2a + 2h) - 4] - [a^2 - 2a - 4]}{h}$$ $$=\lim_{h \rightarrow 0} \frac{h^2 + 2ah + 2h}{h}$$ $$=\lim_{h \rightarrow 0} h + 2a + 2$$ $$= 2a + 2$$

There's your formula for the slope at any value $a$ along the curve $f(x)$

Sorry, I misread your post now I see that you want the equation!

We'll right the formula out in the form $y = mx + b$

Well we can begin with finding the slope of the line at $a = 2$

$$m = 2a + 2$$ $$= 2(2) + 2$$ $$= 6$$

The point at $x = 2$ is $(2,4)$ since if we plug $x = 2$ into $f(x)$ we end up with $y = 4$

So,

$$y = mx+b$$ $$4 = 6(2) + b$$ $$4 - 12 = b$$ $$-8 = b$$

Therefore your equation is:

$$y = 6x - 8$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.